Assessment Of Severity And Identification Of Risk Factors For Extravasation In Neonates Receiving Peripheral Intravenous Therapy - Aslam, Hasnain; Naufil, Syed Imam; Ahmad, Waqas; Javed, Bilal; Chaudhry, Ali Raza; Sabir, Fareeba; Gondal, Mudassar Fiaz (Journal of Neonatal Surgery, 2025)
Introduction:Peripheral Iv Cannulation Is A Tool Used Extensively For The Administration Of Fluids, Medications And Blood Products. Iv Cannulation, Especially In Neonates, Can Result In A Number Of Local And Systemic Complications, One Of Which Is Extravasation Which Merits Further Study. Defined As The Penetration Of Substances Into Surrounding Tissues, It Accounts For 23-78 Percent Of Complications Of Peripheral Iv Cannulation. This Study, Conducted In The Hdu Of Pediatric Surgery Department Of Holy Family Hospital, Aimed To Identify The Risk Factors Associated With Peripheral Iv Access In Neonates. Objectives:The Study Aims To Provide Valuable Information On The Risk Factors For Intravenous Extravasation In This Population And Inform The Development Of Evidence-Based Guidelines And Protocols For The Prevention And Management Of Intravenous Extravasation In Our Set-Up, Improving Patient Outcomes And Reducing Healthcare Costs. Methods:In Compliance With The Guidelines Issued By The Ethical Review Board, A Prospective Observational Study Was Carried Out Over The Span Of Seven Months. Periodic Evaluation Of Over 93 Neonates Was Carried Out Using Standardized Checklists Which Included The Following Parameters, Accumulated By Rigorous Review Of Previously Available Literature. Type Of Infusion, Pre-Existing Infection, Splinting, Body Temperature, Site Of Cannulation And General Hygienic Practices (Diaper Status, Use Of Masks And Sanitizers By Staff And Attendant). Data Obtained Was Then Subject To Analysis Using Spss V23. Results:Multivariate Logistic Regression Analysis Showed That Pre-Existing Infection [Aor 2.25 95% Ci (1.01-5.05)] , Anatomical Site Of Cannula, [Lower Limb Aor 2.77 95% Ci (1.02-7.52), Scalp Aor 2.56 95% Ci (1.02-6.46] (With Upper Limb Taken As Reference)] Types Of Medications Through Iv Route [Antibiotics Aor 2.68 95% Ci (1.2-5.96) Compared To Maintenance/ Resuscitation Fluids ], Had A Statistically Significant Association With The Incidence Of Extravasation In Neonates, While The Presence Or Lack Thereof Of Splinting And Hygienic Measures Did Not Correlate Significantly With Iv Infiltration. Conclusion:Although Numerous, Risk Factors Associated With Intravenous Extravasation Are Easily Avoidable And Can Be Minimized With Appropriate Measures Undertaken By The Concerned Healthcare Staff And Attendants. This, Combined With Better Liaison Between Nurses And Surgeons, Will Not Only Improve Neonatal Outcomes, But Will Also Increase Efficiency Of The Healthcare Machinery.